2021
DOI: 10.1002/path.5774
|View full text |Cite
|
Sign up to set email alerts
|

Cripto favors chondrocyte hypertrophy via TGF‐β SMAD1/5 signaling during development of osteoarthritis

Abstract: Chondrocytes in mice developing osteoarthritis (OA) exhibit an aberrant response to the secreted cytokine transforming growth factor (TGF)-β, consisting in a potentiation of intracellular signaling downstream of the transmembrane type I receptor kinase activin receptor-like kinase (ALK)1 against canonical TGF-β receptor ALK5-mediated signaling. Unfortunately, the underlying mechanisms remain elusive. In order to identify novel druggable targets for OA, we aimed to investigate novel molecules regulating the ALK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Apart from the expression pattern of Grp78, our results showed that the chondrocytes of the proliferating zone were weakly immunopositive to Cripto, while the chondrocytes of the hypertrophic zone were strongly immunopositive to both Cripto and Grp78. A recent study has shown that immunofluoroscene labeling positivity to Cripto was found at the boundaries of the area containing hypertrophic chondrocytes in a metatarsal organ culture derived from E15.5 to E17.5 mouse hind limb [19]. This result indicates that the protein expression pattern of Cripto in the hypertrophic chondrocytes of the SOS would be similar to that of chondrocytes in the endochondral ossification of long bones.…”
Section: Discussionmentioning
confidence: 77%
“…Apart from the expression pattern of Grp78, our results showed that the chondrocytes of the proliferating zone were weakly immunopositive to Cripto, while the chondrocytes of the hypertrophic zone were strongly immunopositive to both Cripto and Grp78. A recent study has shown that immunofluoroscene labeling positivity to Cripto was found at the boundaries of the area containing hypertrophic chondrocytes in a metatarsal organ culture derived from E15.5 to E17.5 mouse hind limb [19]. This result indicates that the protein expression pattern of Cripto in the hypertrophic chondrocytes of the SOS would be similar to that of chondrocytes in the endochondral ossification of long bones.…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, Qu et al demonstrated that high doses of TGF-β contribute to degeneration of nucleus pulposus cells in the intervertebral disc via upregulation of ALK1 and SMAD1/5 [ 121 ]. Moreover, gene expression analysis in experimental OA models and human OA samples showed upregulation of the TGF-β co-receptor Cripto, which participates in a TGF-β-ALK1-Cripto receptor complex, thereby inducing SMAD1/5 signaling in chondrocytes and induction of hypertrophy [ 126 ]. Thus, the impact of increased TGF-β activation in articular cartilage may move from homeostatic SMAD2/3 signaling towards pathological SMAD1/5 signaling, depending on its levels, context and receptor usage.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, these results were also in agreement with data in human primary chondrocytes demonstrating that Sr chondroitin sulfate markedly upregulated the expression of COL2A1 and ACAN ( Ma et al, 2017 ). The TGFβ co-receptor Cripto promoted COL10A1 by inducing SMAD1/5/9 signaling in ATDC5 cells and immortalized C28/12 human chondrocytes ( Garcia de Vinuesa et al, 2021 ). A role for ALPL in the maturation and mineralization as well as the inhibitory effect of Sr on SPP1, COL10A1, and ALPL was reported in murine chondrocytes ( Ehirchiou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%